The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/pam.22054
|View full text |Cite
|
Sign up to set email alerts
|

Who Benefits from Targeted Property Tax Relief? Evidence from Virginia Elections

Abstract: This study examines the market impact of targeted property tax relief, which is critical for understanding who exactly benefits from a widely used local policy. Specifically, we investigate this in the context of two statewide ballot measures in Virginia that provided property tax relief or heightened expectations for future relief intended to aid disabled veterans and seniors, respectively. Using residential multiple listing service microdata from Virginia, results from a regression discontinuity analysis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In addition to the specific policy question of age-based tax exemptions, our results provide additional general evidence that households sort or vote based on tax burdens, conditional on amenities (Oates 1969, Palmon and Smith 1998, Banzhaf and Oates 2013, MacKay 2014, Stadelmann and Eichenberger 2014. Moulton, Waller, and Wentland (2018) have specifically found that age-based tax exemptions in Virginia increase property values, indicating an overall demand shock, but do not consider demographic sorting patterns or housing consumption explicitly.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition to the specific policy question of age-based tax exemptions, our results provide additional general evidence that households sort or vote based on tax burdens, conditional on amenities (Oates 1969, Palmon and Smith 1998, Banzhaf and Oates 2013, MacKay 2014, Stadelmann and Eichenberger 2014. Moulton, Waller, and Wentland (2018) have specifically found that age-based tax exemptions in Virginia increase property values, indicating an overall demand shock, but do not consider demographic sorting patterns or housing consumption explicitly.…”
Section: Introductionmentioning
confidence: 66%
“…Note, however, that we cannot rule out the possibility that there is a causal effect on the overall price function, such as those found byMoulton, Waller, and Wentland (2018). Such effects would be differenced out in the comparison between older and younger households.…”
mentioning
confidence: 81%
“…As an alternate estimation approach, we follow a regression discontinuity design similar to Moulton, Waller, and Wentland (2018), which is broadly consistent with the event study literature in finance and applied microeconomics. This approach combines a hedonic sale price model and a standard dual linear spline RD model, using the date of sale as the running variable.…”
Section: Regression Discontinuity In Time (Rdit) Designmentioning
confidence: 99%
“…While their work acknowledges the presence of cross-sectional dependence, and utilizes a spatial hedonic model in the form of Prucha (1998, 1999) to support their main conclusions, they do not incorporate the dependence into the RD framework itself and admit "…accounting for such cross-sectional interactions in a quasi-experimental framework is challenging and an interesting topic for future research (p. 121)". A similar example comes in the form of Moulton et al (2016) which examines the benefits of targeted property tax relief measures in Virginia, using an RD framework, and finds that increased demand stemming from the measure lead to a 5% increase in home values. Again, acknowledging the possibility of these cross-sectional interactions, they employ a spatial fixed effects specification as a robustness check.…”
Section: Introductionmentioning
confidence: 99%